STATUS OBESITAS ORANG DEWASA MENURUT FAKTOR SOSIO DEMOGRAFI DAN PERILAKU: Studi Kasus di Kota Depok - Sudikno Sudikno; Sandjaja Sandjaja (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2005)
ABSTRACTBackground: Change in eating habits and physical activities of people who live in big cities cause nutritional problem such as obesity. Objectives: This research aims to measure nutritional obesity status and percentage difference of it based on socio-demographic and behavioral factors in Depok, 2004. Methods: A cross-sectional study was conducted to collect data from 399 samples, 199 men and 200 women aged older than 18 years. Sampling method based on rapid assessment that developed by Expanded Program on Immunization/World Health Organization (EPI/WHO). Results: The result showed that there was a significant difference in the proportion of adult obesity between sex, among age groups, and among occupation groups. [Penel Gizi Makan 2005,28(2): 74-82]. Keywords: adult obesity, socio-demographic, habits.